Recent advances in the acute management and long-term secondary prevention in transient ischaemic attack and ischaemic stroke - Kalafatakis, Konstantinos (Pharmakeftiki, 2025)
Ischaemic stroke is by far the most frequent condition that neurologists routinely face in the hospital setting, accompanied by significant morbidity and long-term loss of function for the survivors. The approach of the potential stroke patient should start at the pre-hospital level, since time is of essence. Any focal neurological deficit of sudden onset should raise the suspicion of stroke or transient ischaemic attack (TIA), especially if no signs of seizures are present. After prompt brain imaging, in the setting of the emergency department, treatment mainly aims at reperfusing the tissue originally supplied by the occluded artery. This is achieved by either intravenous thrombolysis or mechanical thrombectomy. Certain criteria must be fulfilled in order to be able to apply these treatments. Moving away from the emergency approach, an important concern of the subacute (in-hospital) and long-term (post-hospitalisation) treatment of stroke patients surrounds the challenges regarding the proper use of antiplatelet and anticoagulant agents. The latter have a place in the long-term secondary prevention of cardioembolic stroke or TIA, while the former (either as a monotherapy or as a dual antiplatelet treatment) are mainly used in the management of the hospitalised patients and the secondary prevention of non-cardioembolic stroke and TIA.